Formulation and Characterization of Herbal Solid Soap Enriched with Cinnamon (Cinnamomum burmanii) and Aloe vera Peel Extracts - Narsih; Y. Erning Indrastuti; Desdy Hendra Gunawan; Saniah; Borneo Satria Pratama (Indonesian Scholar Society, 2025)
This study aims to develop a solid soap formulation using natural ingredients by combining cinnamon (Cinnamomum burmanii) extract and Aloe vera peel extract, which are known for their antibacterial, antioxidant, and moisturizing properties. The research involved several stages, including the extraction of cinnamon and Aloe vera, soap formulation with varying cinnamon and Aloe vera extract concentrations, and testing of physicochemical properties and antibacterial activity against Escherichia coli. The formulated soaps were evaluated for moisture content, free alkali levels, pH, foam stability, antibacterial inhibition zones, and skin irritation. The results showed that increasing the concentrations of cinnamon and Aloe vera peel extracts significantly affected the soap’s characteristics. The optimal formulation was obtained with 15% cinnamon extract and 6% Aloe vera peel extract (A3B3), yielding a moisture content of 2.44%, free alkali content of 1.70%, pH of 11.8, and an antibacterial inhibition zone of 1.28 mm, without any skin irritation. FTIR analysis identified functional groups such as aldehydes, alkanes, aromatics, and hydroxyls, which were associated with the bioactive compounds responsible for antibacterial and moisturizing effects. The presence of cinnamaldehyde in cinnamon and saponins in Aloe vera contributed to the soap’s enhanced antimicrobial and skin-conditioning properties. Furthermore, Fourier-transform infrared spectroscopy (FTIR) analysis identified key functional groups responsible for the soap’s bioactivity. These findings suggest that incorporating herbal extracts into soap formulations can improve their functional benefits, making them a promising alternative for natural skincare products with antibacterial protection and skin health benefits.